New directions in treatment of the ischemic stroke - Bartłomiej Zaremba; Adrianna Gorecka; Olga Wysokińska; Krystian Cholewa; Joanna Milanowska (Kazimierz Wielki University, 2020)
Stroke remains a leading cause of death and disability worldwide. The cause is decrease or total blocking of blood perfusion in brain and fast recognition is essential to conduct proper treatment. Currently commonly used methods are thrombolysis and mechanical thrombectomy, which high efficacy is observed only if they are performed within a few hours of the first symptoms. Hence loads of people, who are diagnosed later, become unable to undergo effective treatment. In the study are presented pathogenesis, epidemiology, classification, diagnosis and current treatment of the disease, but the main aim of the study is to present the results of the reports on new treatments for ischemic stroke. The research method is a review of the available literature published in PubMed, UpToDate and Google scholar databases. In the study were reviewed new methods, which can be alternative for currently used ones. They are small molecules including fluoxetine, aripiprazole, L-DOPA, cholinergic and noradrenergic drugs, growth factors (HCG, EPO), monoclonal antibodies, allogenic stem cells, neurostimulators,  robotic therapy and telerehabilitation. They give hope for curing a larger number of patients and improving effects of rehabilitation after ischemic stroke. However most of the methods, which are presented in this study require the use of tests that will allow checking their safety and application.